Assessing Disability Magnitude using Whodas in Schizophrenia Patients in A Regional Mental Health Hospital - Sitti Rahma Soleman; Lailaturohmah Kurniawati; Laras Putri Yani; Meli Nur Atika Putri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a chronic mental disorder that significantly contributes to global disability. Schizophrenia patients experience impairments in multiple functional areas such as cognition, mobility, self-care, social interaction, and participation in daily life activities. Evaluating the magnitude of these disabilities is crucial for designing targeted interventions and improving patient outcomes. Objective: This study aims to assess the level of disability in schizophrenia patients using the WHO Disability Assessment Schedule (WHODAS 2.0) at Dr. Arif Zainudin Regional Psychiatric Hospital, Surakarta. Method: A quantitative descriptive study using an observational-analytic approach was conducted with 106 patients with schizophrenia. Data were collected using the WHODAS 2.0 questionnaire, which assesses six functional domains: cognition, mobility, self-care, getting along, life activities, and participation. Data were analyzed using SPSS 26 software. Results: The study found that usual to mild impairment was observed in all domains. Cognitive impairments were seen mainly in problem solving and concentration. Mobility and self-care tasks were manageable, but independence was slightly impaired. Social interaction and community participation were limited by emotional and environmental factors. Conclusions: Patients with schizophrenia exhibit mild disability across multiple domains, particularly in social and emotional aspects, highlighting the need for targeted interventions to improve their functional outcomes.